Associations between transcranial direct current stimulation session exposure and clinical outcomes in knee osteoarthritis: a cross-sectional analysis exploring the role of pain catastrophizing - Ravi Shankar Reddy; Jaya Shanker Tedla; Shaker Hassan S. Alshehri; Faisal M Alyazedi; Suhail Mansour Aljehani; Feras Ahmed Alarabi (Journal of Orthopaedic Surgery and Research)
Abstract Background Knee osteoarthritis (KOA) is a prevalent musculoskeletal disorder characterized by chronic pain, reduced physical function, and impaired quality of life. Transcranial direct current stimulation (tDCS) has emerged as a promising non-invasive neuromodulatory intervention, yet limited evidence exists regarding its association with clinical outcomes and the role of psychological mediators in this population. This cross-sectional study investigated the relationship between tDCS parameters (number of sessions, stimulation intensity, and duration) and clinical outcomes—pain, functional disability, and quality of life—in individuals with KOA, and explored whether pain catastrophizing mediates these associations. Methods Sixty-eight participants diagnosed with KOA and treated with tDCS were enrolled. Clinical outcomes were assessed using the Numeric Pain Rating Scale (NPRS), KOOS-Physical Function Shortform (KOOS-PS), and EQ-5D-5 L index. Pain catastrophizing was measured using the Pain Catastrophizing Scale (PCS). Pearson correlations, multiple linear regression, and mediation analysis using the PROCESS macro were performed. A p-value < 0.05 was considered statistically significant. Results The number of tDCS sessions showed significant correlations with reduced pain (r = − 0.42, p = 0.002), improved function (r = 0.39, p = 0.004), and better quality of life (r = 0.44, p = 0.001). Regression analysis showed that the number of tDCS sessions was significantly associated with NPRS (β = − 0.36, p = 0.004), KOOS-PS (β = 0.33, p = 0.005), and EQ-5D-5 L (β = 0.42, p = 0.001). Pain catastrophizing partially mediated these associations, with significant indirect effects observed for all outcomes (p < 0.05). Conclusion Higher tDCS session frequency was correlated with favorable clinical outcomes in KOA, and pain catastrophizing showed statistical evidence of an indirect association, though no causal mediation can be inferred. These findings highlight the importance of considering psychological factors in neuromodulatory treatment planning.